2019
DOI: 10.1007/s40620-019-00652-9
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and clinical outcomes in patients with non-dialysis dependent or dialysis dependent severe chronic kidney disease: a Danish population-based study

Abstract: Background Routine clinical evidence is limited on clinical outcomes associated with anemia in patients with severe chronic kidney disease (CKD). Methods We linked population-based medical databases to identify individuals with severe CKD (eGFR < 30 mL/ min/1.73 m 2) in Northern Denmark from 2000 to 2016, including prevalent patients as of 1 January 2009 or incident patients hereafter into the study. We classified patients as non-anemic (≥ 12/≥ 13 g/dl hemoglobin (Hgb) in women/men), anemia grade 1 (10-12/13 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 30 publications
(30 reference statements)
10
34
0
Order By: Relevance
“…Observational studies have shown that patients with anemia of NDD-CKD frequently have a high incidence of adverse clinical outcomes. 9 In OLYMPUS, the safety profile of roxadustat was comparable to placebo, as was seen in previous placebo-controlled roxadustat studies. [37][38][39] More patients receiving roxadustat who had low eGFR or initiated dialysis, which are associated with higher risk of death and cardiovascular events, [6][7][8] remained on roxadustat versus placebo.…”
Section: Discussionsupporting
confidence: 68%
“…Observational studies have shown that patients with anemia of NDD-CKD frequently have a high incidence of adverse clinical outcomes. 9 In OLYMPUS, the safety profile of roxadustat was comparable to placebo, as was seen in previous placebo-controlled roxadustat studies. [37][38][39] More patients receiving roxadustat who had low eGFR or initiated dialysis, which are associated with higher risk of death and cardiovascular events, [6][7][8] remained on roxadustat versus placebo.…”
Section: Discussionsupporting
confidence: 68%
“…The paper by Toft et al [8] is in line with previous findings coming from older cross-sectional studies [9]. Given its longitudinal design, it allows to detect also the incidence of anaemia over time and its burden on outcomes.…”
Section: Do These Findings Add New Knowledge?supporting
confidence: 68%
“…Toft et al [8] presented the findings of a population-based study performed in Northern Denmark on anaemia and clinical outcomes in CKD. Data were obtained linking Danish population-based healthcare and administrative databases.…”
Section: Is There Still a Role For Observational Studies?mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known that nutritional status, particularly serum albumin, is strongly associated with mortality in HD patients 33,34 . Anemia was also associated with all‐cause mortality in patients with CKD either with or without dialysis dependence 35 . Thus, ensuring adequate dialysis clearance could improve the nutritional status, anemia, and mortality of HD patients.…”
Section: Discussionmentioning
confidence: 99%